2018
DOI: 10.1021/acsanm.7b00087
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Conjugated Halloysite Nanotubes, an Efficient Drug Carrier, Deliver Doxorubicin for Targeted Therapy of Breast Cancer

Abstract: To carry doxorubicin (DOX) on breast cancer site effectively, halloysite nanotubes conjugated with poly­(ethylene glycol) and folate (HNTs-PEG-FA) is designed as a targeted drug delivery system. Halloysite nanotubes (HNTs) are shortened to ∼200 nm by ultrasonic scission and functionalized with amide groups to conjugate with N-hydroxylsuccinimide-polyethylene glycol carboxylic acid (NHS-PEG-COOH) and folate (FA). DOX@HNTs-PEG-FA is prepared by loading DOX on HNTs-PEG-FA via physical adsorption. The sustained an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 66 publications
1
68
0
Order By: Relevance
“…FA-conjugated chitosan oligosaccharide-magnetic HNTs were studied as a delivery system for camptothecin, an anti-cancer drug [ 37 ]. Wu et al (2018) also functionalized the HNT surface with APTES for conjugation of PEG and folic acid and subsequently loaded HNTs with doxorubicin [ 38 ]. The limitation of their study was the reported low drug loading efficiency, which was only 3%.…”
Section: Discussionmentioning
confidence: 99%
“…FA-conjugated chitosan oligosaccharide-magnetic HNTs were studied as a delivery system for camptothecin, an anti-cancer drug [ 37 ]. Wu et al (2018) also functionalized the HNT surface with APTES for conjugation of PEG and folic acid and subsequently loaded HNTs with doxorubicin [ 38 ]. The limitation of their study was the reported low drug loading efficiency, which was only 3%.…”
Section: Discussionmentioning
confidence: 99%
“…However, HNTs negatively charged surface (−16.5 ± 1.2 mV) requires positively charged drugs to bind, restricting the binding opportunity for negatively charged drugs. In another study, HNTs were conjugated with poly(ethylene glycol) (PEG) and folate (FA) to formulate HNTs-PEG-FA complexes for targeted DOX delivery into breast tumors [ 47 ]. HNTs-PEG-FA complexes possessed only 3% DOX loading efficiency and almost 35% cell viability for 8.0 × 10 3 MCF-7 cells/well at a concentration of 10 µg/mL DOX.…”
Section: Discussionmentioning
confidence: 99%
“…The DOXO@ HNTs-PEG-FA reduced toxicity and inhibited tumour growth associated with higher levels of caspase-3 protein. These results suggest that FA-conjugated HNTs may be designed to be a novel drug delivery system for targeted therapy of breast cancer via intravenous [9]. Diagram for the preparation of DOX@ZIF-HA and the Fe 3+ -mediated coordination interaction between HA and PDA [8].…”
Section: Drug Delivery 21 Anti-cancermentioning
confidence: 95%